USE OF ESSENTIAL OILS FOR FOOD SAFETY: FORMULATIONS OF EASY-TO-USE FOOD-GRADE SPRAY SANITIZERS - Farasoa, Helga (Food and Feed Research, 2023)
Motivated by combat against the spread of foodborne diseases, the formulations of simple and easy-to-use spray disinfectants containing Cinnamomum zeylanicum and Ocimum gratissimum essential oils were studied. Central composite experimental design was used in the development of stable products with optimal essential oil content for antimicrobial efficacy. It also allowed minimizing the alcohol content which was used to ensure miscibility between the essential oils and the aqueous phase. Trans-cinnamaldehyde was the major compound in the C. zeylanicum essential oil. Its low toxicity allowed the formulation of a risk-free product despite the great variability in the chemical composition of the essential oil. Cooked food coated with a spray containing 1% of this essential oil, in combination with Thymus vulgaris tincture, could be preserved for 3 days without refrigeration. Eugenol was the major component of O. gratissimum essential oil, followed by 1,8- cineole and methylchavicol. Sprays containing 1.5% of this essential oil were effective against Escherichia coli and Staphylococcus aureus. Xanthan gum proved to be a good essential oil-trapping agent under accelerated ageing conditions at 45 °C.